Implementation of the Van Meter and Van Horn Zoning System Policies Model - Rolifola Cahya Hartawan; Fitriyani Kosasih (CV. AFDIFAL MAJU BERKAH, 2023)
This research is motivated by the phenomenon of the policy phenomenon of the New Student Admission Zoning System which causes pros and cons in society. Some people argue that this system is unfair for high achieving students but cannot enter the favorite school that was previously intended. On the other hand, the community argues that this system is beneficial for students who live in favorite schools.The approach used in this research is qualitative with descriptive analysis method. The purpose of this study is to see and describe the implementation of the Van Meter and Van Horn policy models. The results of this study are: 1) Implementation and communication activities between policy implementing organizations have been implemented, but the results have not been optimal, 2) The characters of SMAN 2 Bandung as implementers have understood the policy context well, are consistent with the goals and objectives and Policy objectives, implement prospective students firmly and strictly on policy rules, and supervise Zoning System policies in accordance with PPDB technical guidelines and SOPs but the results are optimal, 3) The disposition as policy implementers has not seen what to do, has the ability to do these policies and have the commitment to implement PPDB policies for optimal system zoning systems, 4) Social, economic and political conditions have influenced policy policies, 5) The zoning of system policy implementation has a positive impact on service policies and the quality of education services. The conclusion of this research is that SMAN 2 Bandung has implemented a zoning system policy but it has not been optimal.